A wide-range operating synaptic device based on organic ferroelectricity with low energy consumption. Issue 47 (25th July 2018) - Tu, Li; Yuan, Sijian; Xu, Jiawei; Yang, Kunlong; Wang, Pengfei; Cui, Xiaolei; Zhang, Xin; Wang, Jiao; Zhan, Yi-Qiang; Zheng, Li-Rong
Abstract : The two-terminal synaptic device based on organic ferroelectricity with low energy consumption can provide reliable synaptic function. Abstract : In this work, a wide-range operating synaptic device based on organic ferroelectricity has been demonstrated. The device possesses a simple two-terminal structure by using a ferroelectric phase-separated polymer blend as the active layer and gold/indium tin oxide (ITO) as the top/bottom electrodes, and exhibits a distinctive history-dependent resistive switching behavior at room temperature. And the device with low energy consumption (∼50 fJ μm −2 per synaptic event) can provide a reliable synaptic function of potentiation, depression and the complex memory behavior simulation of differential responses to diverse stimulations. In addition, using simulations, the accuracy of 32 × 32 pixel image recognition is improved from 76.21% to 85.06% in the classical model Cifar-10 with 1024 levels of the device, which is an important step towards the higher performance goal in image recognition based on memristive neuromorphic networks.